2018
DOI: 10.3390/bios8040128
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Nanoparticle-Based Biosensing Assay Quantitatively Enhances Acid-Fast Bacilli Count in Paucibacillary Pulmonary Tuberculosis

Abstract: A new method using a magnetic nanoparticle-based colorimetric biosensing assay (NCBA) was compared with sputum smear microscopy (SSM) for the detection of pulmonary tuberculosis (PTB) in sputum samples. Studies were made to compare the NCBA against SSM using sputum samples collected from PTB patients prior to receiving treatment. Experiments were also conducted to determine the appropriate concentration of glycan-functionalized magnetic nanoparticles (GMNP) used in the NCBA and to evaluate the optimal digestio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 27 publications
1
26
0
Order By: Relevance
“…The images show that the GMNP aggregates and concentrates the AFB when using NCBA ( Figure 6A); the same sample registered negative (no visible red AFB) when using SSM ( Figure 6B). Our previous study showed that NCBA increased AFB count by 47% compared to SSM [33].…”
Section: Ncba Vs Ssm Vs Culturementioning
confidence: 89%
See 4 more Smart Citations
“…The images show that the GMNP aggregates and concentrates the AFB when using NCBA ( Figure 6A); the same sample registered negative (no visible red AFB) when using SSM ( Figure 6B). Our previous study showed that NCBA increased AFB count by 47% compared to SSM [33].…”
Section: Ncba Vs Ssm Vs Culturementioning
confidence: 89%
“…The images show that the GMNP aggregates and concentrates the AFB when using NCBA ( Figure 6A); the same sample registered negative (no visible red AFB) when using SSM ( Figure 6B). Our previous study showed that NCBA increased AFB count by 47% compared to SSM [33]. Using a medical statistical software (available online: https://www.medcalc.org/calc/diagnostic_test.php, accessed on 11 December 2019), the clinical sensitivity, clinical specificity, positive predictive value, and negative predictive value were calculated and presented in Table 2.…”
Section: Ncba Vs Ssm Vs Culturementioning
confidence: 99%
See 3 more Smart Citations